IMPACTS OF PATTERNS OF ECONOMIC AGENTS ACTIVITIES IN THE SEMERU VOLCANO CONSERVATION AREA - Nuansa Bayu Segara; Iin Wariin Basyari (JURNAL GEOGRAFI, 2021)
Semeru volcano is the most popular mount hiking tourism in Indonesia. The economic community and conservation area are affected by these activities. This research focuses on the development activities of economic agents pattern and explains the impact of high tourism in the Semeru Volcano conservation area. It was a qualitative study, and the participative observatory was a procedure for collecting the data. The location was not limited in the Semeru Volcano, but also social media, Instagram. The result of the research reveals that there are two kinds of economic agents, namely internal and external. They have positive connectedness to support hiking activities. Although there should be potential for competition between open trip services and local guides, this does not happens, due to the wisdom of internal economic actors, especially local guides. Moreover, the consequences of high tourism activities in the Semeru Volcano conservation area are waste and erosion. The article is concluded by proposing several directions for economic agents to be involved more in conservation activities and positive business in the Semeru Volcano.Key words: Semeru Volcano, economic agent, conservation area, mount tourismGunungapi Semeru merupakan wisata pendakian gunung yang paling populer di Indonesia. Aktivitas ini tentu berdampak terhadap perekonomian penduduk sekitar dan lingkungan di kawasan konservasi. Artikel ini mengkaji pola aktivitas dan pelaku ekonomi yang terlibat dalam perkembangan wisata, dan mengungkap dampak tingginya aktivitas ini terhadap Kawasan Konservasi Gunungapi Semeru itu sendiri. Penelitian ini menggunakan pendekatan kualitatif yang bersifat ekploratif. Pengumpulan data dilakukan secara observasi partisipatif dan tidak terbatas di kawasan pendakian, namun juga melakukan observasi di media sosial instagram. Hasil penelitian menujukan pelaku ekonomi terdiri dari internal dan eksternal kawasan, yang memiliki keterkaitan positif antar pelaku ekonomi dari luar dan dalam Kawasan Pendakian. Meskipun semestinya ada potensi persaingan antara jasa open trip dengan pemandu lokal, akan tetapi hal itu tidak terjadi, karena kearifan pelaku ekonomi internal, khususnya para pemandu lokal. Dampak tingginya aktivitas wisata pendakian ini mengakibatkan dua permasalahan yang cukup serius, yaitu sampah dan erosi. Artikel ini diakhiri dengan memberikan beberapa usulan terkait dengan peningkatan keterlibatan pelaku ekonomi dalam melakukan usaha dan aktivitas konservasi di Kawasan Gunung Semeru. Kata kunci: Gunungapi Semeru, pelaku ekonomi, kawasan konservasi, wisata gunung